Efficacy and Safety of the FOLFOX4 Regimen Versus Doxorubicin in Chinese Patients With Advanced Hepatocellular Carcinoma: A Subgroup Analysis of the EACH Study. (15th September 2014) - Qin, Shukui; Cheng, Ying; Liang, Jun; Shen, Lin; Bai, Yuxian; Li, Jianfeng; Fan, Jia; Liang, Lijian; Zhang, Yaqi; Wu, Gang; Rau, Kun‐Ming; Yang, Tsai‐Shen; et al.
Abstract : Background: The EACH study assessed the efficacy of oxaliplatin, 5‐fluorouracil, and leucovorin (the FOLFOX4 regimen) compared with doxorubicin alone in terms of overall survival (OS), progression‐free survival (PFS), and safety in patients with advanced hepatocellular carcinoma (HCC). We present the results of this study in Chinese patients. Methods: In a multicenter, open‐label, randomized, phase III study (00471965 ), 371 patients (279 patients from the People's Republic of China) were randomized 1:1 to receive either FOLFOX4 or doxorubicin until disease progression, intolerable toxicity, death, or surgical resection. Results: Baseline characteristics of the Chinese patients enrolled in the study were similar for the 2 treatment groups and in comparison with the whole EACH cohort. Median OS at the prespecified time point of treatment was 5.7 months with FOLFOX4 and 4.3 months with doxorubicin (hazard ratio [HR]: 0.74; 95% confidence interval [CI]: 0.55–0.98; p = .03). At the end of the follow‐up period, median OS was 5.9 months with FOLFOX4 and 4.3 months with doxorubicin (HR: 0.75; 95% CI: 0.58–0.98; p = .03). Median PFS was 2.4 months and 1.7 months in the FOLFOX4 and doxorubicin groups, respectively (HR: 0.55; 95% CI: 0.45–0.78; p = .0002). The response rate (RR) and disease control rate (DCR) were significantly higher in the FOLFOX4 group than in the doxorubicin group (RR: 8.6% vs. 1.4%, p = .006; DCR: 47.1% vs. 26.6%, p = .0004). Hematological toxicity was more frequently reported in the FOLFOX4 group. Conclusion: For Chinese HCC patients enrolled in the EACH study, FOLFOX4 significantly improved the RR and DCR and prolonged survival compared with doxorubicin. Systemic chemotherapy with oxaliplatin‐based regimens may play an important role in the treatment of Chinese patients with advanced HCC. Abstract : The authors report the results of the EACH study for the subgroup of Chinese patients with advanced hepatocellular carcinoma (HCC) who are ineligible for curative resection or local treatment. FOLFOX4 significantly improved response and disease‐control rates and prolonged survival compared with doxorubicin. Systemic chemotherapy with oxaliplatin‐based regimens may play an important role in the treatment of Chinese patients with advanced HCC. Abstract : 摘要 背景 . EACH 研究评估了 FOLFOX4 方案（奥沙利铂、5‐氟尿嘧啶和亚叶酸）与多柔比星单药治疗进展期肝细胞癌（HCC）患者的有效性 [包括总生存（OS）和无进展生存（PFS）]和安全性。本文介绍了 EACH 研究的中国患者结果。 方法 . EACH 研究是一项多中心、开放标签的 III 期随机临床试验（ 00471965 ），371 例患者（其中 279 例来自中国大陆）按 1:1 比例随机分配，接受 FOLFOX4 方案或多柔比星单药治疗，直至疾病进展、发生不可耐受的毒性事件、死亡或接受手术切除。 结果 . 中国招募的患者中两个治疗组的基线特征相似，中国患者人群的基线特征与 EACH 研究总队列也相似。在计划的治疗时间内，FOLFOX4 方案与多柔比星的中位 OS 分别为 5.7 个月和 4.3 个月 [风险比（HR）：0.74；95% 可信区间（CI）：0.55 ∼ 0.98， P = 0.03]。随访结束时，FOLFOX4 方案与多柔比星的中位 OS 分别为 5.9 个月和 4.3 个月（HR：0.75，95%CI ：0.58 ∼ 0.98； P = 0.03）。FOLFOX4 组和多柔比星组的中位 PFS 分别为 2.4 个月和 1.7 个月（HR：0.55；95%CI ：0.45 ∼ 0.78； P = 0.0002）。FOLFOX4 组的缓解率（RR）和疾病控制率（DCR）显著高于多柔比星组（RR：8.6% vs. 1.4%， P = 0.006 ；DCR：47.1% vs. 26.6%， P = 0.0004）。FOLFOX4 方案组中血液学毒性更常见。 结论 . 与多柔比星相比，FOLFOX4 方案显著提高 EACH 研究入组的中国 HCC 患者的 RR 和 DCR，并延长了生存期。以奥沙利铂为基础的全身化疗方案在中国进展期 HCC 患者的治疗方面可能具有重要作用。 The Oncologist 2014;19: 1169‐1178